2013
DOI: 10.2807/1560-7917.es2013.18.39.20594
|View full text |Cite
|
Sign up to set email alerts
|

Unusual increase in reported cases of Paratyphoid A fever among travellers returning from Cambodia, January to September 2013

Abstract: From January to September 2013, a marked increase in notifications of Salmonella Paratyphi A infections among travellers returning from Cambodia occurred in France. An investigation revealed 35 cases without a common source: 21 in France, five in Germany, three in the Netherlands, one in Norway, one in the United Kingdom, four in New-Zealand. Data suggest an ongoing event that should trigger further investigation. Travellers to Cambodia should observe preventive measures including good personal hygiene and foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…At that time, Paratyphi A was relatively common in North America (12). Today, Paratyphi A accounts for a sizable fraction (14-64%) of all enteric fever in India, Pakistan, Nepal, Indonesia, and China (13)(14)(15)(16), but has largely disappeared from Europe and North America, except for travelers returning from South and Southeast Asia (17,18). Otherwise, little is known about its historical patterns of spread or its evolutionary history.…”
mentioning
confidence: 99%
“…At that time, Paratyphi A was relatively common in North America (12). Today, Paratyphi A accounts for a sizable fraction (14-64%) of all enteric fever in India, Pakistan, Nepal, Indonesia, and China (13)(14)(15)(16), but has largely disappeared from Europe and North America, except for travelers returning from South and Southeast Asia (17,18). Otherwise, little is known about its historical patterns of spread or its evolutionary history.…”
mentioning
confidence: 99%
“…Between January and September 2013, an unusual increase in the number of Salmonella Paratyphi A infections was registered in adult patients attending Sihanouk Hospital Centre of HOPE (SHCH), in Phnom Penh, Cambodia [2]. A similar trend was noted in travellers returning from Cambodia [3]. These findings were shared with the national health authorities and an epidemiological investigation was initiated; up to now, no common source or specific transmission route has been identified.…”
Section: Dear Editormentioning
confidence: 52%
“…11,12 In 2013, an increase in cases of paratyphoid fever in travelers returning from Cambodia was reported, and all isolates were sensitive to fluoroquinolones. 13 Shwe and others reported that S. typhi was most commonly isolated from blood cultures among children admitted to a hospital in Yangon, 14 and all isolates were sensitive to nalidixic acid. However, there was no case of S. Paratyphi in this report.…”
Section: Discussionmentioning
confidence: 99%